Mechanical and propelling efficiency in swimming derived from exercise using a laboratory-based whole-body swimming ergometer - Zamparo, P.; Swaine, I. L. (Journal of Applied Physiology, 2012)
Determining the efficiency of a swimming stroke is difficult because different "efficiencies" can be computed based on the partitioning of mechanical power output (W.) into its useful and nonuseful components, as well as because of the difficulties in measuring the forces that a swimmer can exert in water. In this paper, overall efficiency (nO = W.TOT/E., where W.TOT is total mechanical power output, and E. is overall metabolic power input) was calculated in 10 swimmers by means of a laboratory-based whole-body swimming ergometer, whereas propelling efficiency (nP = W.D/W.TOT, where W.D is the power to overcome drag) was estimated based on these values and on values of drag efficiency (nD = W.D/E.): nP = nD/nO. The values of nD reported in the literature range from 0.03 to 0.09 (based on data for passive and active drag, respectively). nO was 0.28 ± 0.01, and nP was estimated to range from ~0.10 (nD = 0.03) to 0.35 (nD = 0.09). Even if there are obvious limitations to exact simulation of the whole swimming stroke within the laboratory, these calculations suggest that the data reported in the literature for nO are probably underestimated, because not all components of W.TOT can be measured accurately in this environment. Similarly, our estimations of nP suggest that the data reported in the literature are probably overestimated.